PROSPECTS FOR USING THE CALCULATION PROCEDURE FOR DETERMINING THE FORCES AND MEANS OF RESCUE OF THE SUFFICIENT IN EMERGENCY AND CRISIS SITUATIONS, RELATED TO A STRONG EARTHQUAKE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the role and prospects of using the calculation method for determining the forces and means of rescuing victims in emergency and crisis situations associated with a strong earthquake in the territory of the Republic of Uzbekistan. And also the order of actions of the State System of emergency prevention and actions in such situations of the Republic of Uzbekistan (hereinafter – the State Emergency Service) under the operating modes is given.